Enzymatic Glucose Fiber Sensor for Glucose Concentration Measurement with a Heterodyne Interferometry - Hsu, Cheng-Chih; Chung, Wan-Yu; Chang, Chun-Yi; Wu, Chyan-Chyi; Lee, Cheng-Ling (Sensors (Basel, Switzerland), 2023)
In this study, we developed a glucose fiber sensor incorporating heterodyne interferometry to measure the phase difference produced by the chemical reaction between glucose and glucose oxidase (GOx). Both theoretical and experimental results showed that the amount of phase variation is inversely proportional to glucose concentration. The proposed method provided a linear measurement range of the glucose concentration from 10 mg/dL to 550 mg/dL. The experimental results indicated that the sensitivity is proportional to the length of the enzymatic glucose sensor, and the optimum resolution can be obtained at a sensor length of 3 cm. The optimum resolution of the proposed method is better than 0.6 mg/dL. Moreover, the proposed sensor demonstrates good repeatability and reliability. The average relative standard deviation (RSD) is better than 10% and satisfied the minimum requirement for point-of-care devices.